Influenza A(H5N1) Virus Infections in 2 Free-Ranging Black Bears (Ursus americanus), Quebec, Canada - Benjamin T. Jakobek; Yohannes Berhane; Marie-Soleil Nadeau; Carissa Embury-Hyatt; Oliver Lung; Wanhong Xu; Stéphane Lair (Emerging Infectious Diseases, 2023)
Wholly Eurasian highly pathogenic avian influenza H5N1 clade 2.3.4.4b virus was isolated from 2 free-ranging black bears with meningoencephalitis in Quebec, Canada. We found that isolates from both animals had the D701N mutation in the polymerase basic 2 gene, previously known to promote adaptation of H5N1 viruses to mammal hosts.